Tonal Norm of Government Responses to Citizens’ Appeals - M. A. Shirinkina (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The textual category of tonality is considered in the aspect of normativity on the material of response business letters of administrative content. The question is raised about the norm of speech realization of tonality within the framework of this epistolary subgenre. The normative tonality of official responses to citizens' appeals is formed on the basis of a statement of positive facts and logically emotiveness expressed by typed language means and etiquette formulas of business speech. The novelty of the study is related to the consideration of the response business letter based on a citizen's initiative letter (as part of a text pair of letters), as well as the definition of the field composition and communicative content of the tonality category of the subgenre under consideration. The subject-conceptual and dialogue composition of the text of the letter is distinguished, the correct implementation of tonality is demonstrated with a positive resolution of the conflict and in a more complex business situation. Special attention is paid to tonal disharmony in the authority’s responses to citizens’ appeals. The article presents a list of the author’s speech actions, the side effect of which is the undesirable tonality of the business text (excessive use of legal terms and quoting regulations, use of tokens of undefined semantics, communication of unnecessary information, lack of personification, etc.). The importance of tonally correct design of the response business letter is emphasized.